The Effect of Social Media Promotion on Customer Loyalty Mediated by Brand Equity at Dekabeads - sherli rahmania; Apriansyah Putra (Universitas Islam Indragiri, 2026)
The increasingly dynamic competition in the handmade accessories retail sector encourages SMEs to manage promotional strategies more effectively in order to retain customers. Social media has become one of the primary channels for shaping brand perception and value, which ultimately influence customer loyalty. This study aims to examine the effect of social media promotion on customer loyalty using the Brand Equity framework proposed by Aaker and Keller, with a case study of Dekabeads. The research adopts a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The respondents consist of 169 customers who have previously made purchases. The results indicate that social media promotion has a significant effect on customer engagement, brand equity, customer satisfaction, and customer loyalty. Directly, social media promotion is proven to enhance customer loyalty. In addition, there are indirect effects through increased customer engagement, strengthened brand equity, and improved customer satisfaction as mediating variables. The R-square value of 0.748 indicates that the model explains 74.8% of the variance in customer loyalty. These findings highlight that optimizing social media promotion in alignment with brand equity development plays a crucial role in fostering sustainable customer loyalty.